Structură socială și etnicitate - Paula Tufiș (Sociologie Românească, 2001)
The paper attempts a theoretical and empirical analysis of the relationship between ethnic affiliation, social stratification and ethnic attitudes in Central and Eastern Europe, and in Romania in particular. In the first part of the paper I examine the main theoretical constructs involved in explaining the relationship between stratification and ethnic affiliation, ethnic stratification and class stratification, and the role of market mechanisms in the dynamics of social and ethnic stratification. In order to validate the proposed hypotheses 1 use data regarding former communist countries in Central and Eastern Europe For the Romanian case I employ a multilevel analysis by using regional, community and individual level data.